Activity of non-parliamentary opposition communities in social networks in the context of the Russian 2016 parliamentary election. Issue 4 (2nd October 2018) - Myagkov, Mikhail; Shchekotin, Evgeniy V.; Kashpur, Vitaliy V.; Goiko, Vyacheslav L.; Baryshev, Alexey A.
ABSTRACT: This article aims to analyse the connection between the election to the Russian State Duma in September 2016 and the social network activity of members of the two non-parliamentary opposition groups: right-wing radicals and supporters of the opposition leader Alexei Navalny. For this purpose, the Right-Wing Online Activity Index and Navalny Supporters' Online Activity Index were calculated. Then, using correlation analysis, relationships between the indices and the results of voting for political parties in the election to the State Duma were determined. As a result, the highest values of the Right-Wing and Navalny Supporters' Online Activity Indices were registered in Moscow and St. Petersburg.